Mineral-impregnated carbon-fiber (MCF) composites made with differently sized fly-ash geopolymers for durable light weight and high temperature applications. (April 2023) - Zhao, Jitong; Liebscher, Marco; Köberle, Thomas; Almanla, Ahmad; Mechtcherine, Viktor
Abstract: For a wide application of carbon-fiber reinforcement in large-scaled, lightweight construction, mineral-impregnated carbon-fiber (MCF) composites provide a promising alternative to rebar or reinforcement made of non-metallic fibers and polymer matrix. The penetration ability of the aluminosilicate particles is a key factor for a stable, reproducible impregnation and the maximal reinforcing efficiency of continuous fiber geopolymer composites. The work at hand focuses on the influence of the particle sizes of geopolymer precursors on the processing quality, microstructural development and final composite performance regarding the flexural, tensile and pullout behavior. Three differently sized fly ash (FA) sources were used to impregnate a carbon fiber heavy tow before curing at 75 °C. FA particles in the same size range as the filament diameter proved to be the most efficient, enhancing both mechanical properties of MCF and its bond to concrete matrix, well beyond the effects induced by other, coarser precursors. The results of the microscopic investigation, μCT, thermal gravimetric analyzes and mercury intrusion porosimetry measurements show that the use of this particle fraction resulted in the best fiber-matrix distribution over the cross-section, densest microstructure and highest fiber volume fraction in the impregnated yarn. Furthermore, the geopolymerization kinetics of all FAs at ambient temperature and at 75 °C were determined by isothermal calorimeter, showing an increase in the reaction rate with elevated curing temperature and higher particle finesse.